KEGIATAN PEMASANGAN TITIK KUMPUL DENGAN SIMULASI TANGGAP DARURAT DI SMPN 19 PENAJAM PASER UTARA - Dian Amelia Putri; Jane Monica Devi Alifia Sheren; Hosea Novfianto; Duwy Rahmat Arbianto; Azzis Ramzumar Mahfud; Ari Pujangga Pangestu; Anisa Wisnu Wardhani; Afni Asmaningsih; Elya Rozana Usman; Rika Istianingrum; Mahmudatul Munawaroh (Jurnal Humaniora & Sosial Sains, 2024)
One important step in planning an emergency simulation is to establish a muster point. During an emergency, a muster point is where people gather to maintain safety and avoid confusion. Establishing a muster point means choosing a strategic location, putting up clear identifying signs, and providing information to people who live there and people who come there. A muster point can reduce losses in an emergency situation. Muster point also educate people on the importance of evacuation and local safety. Therefore, planning and implementing activities to establish muster points is a good step to improve emergency preparedness and responsibility.